2022
DOI: 10.3390/life13010009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms in the Vascular and Nervous Systems following Traumatic Spinal Cord Injury

Abstract: Traumatic spinal cord injury (SCI) induces various complex pathological processes that cause physical impairment and psychological devastation. The two phases of SCI are primary mechanical damage (the immediate result of trauma) and secondary injury (which occurs over a period of minutes to weeks). After the mechanical impact, vascular disruption, inflammation, demyelination, neuronal cell death, and glial scar formation occur during the acute phase. This sequence of events impedes nerve regeneration. In the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 122 publications
0
6
0
Order By: Relevance
“…Vascularization facilitates nerve regeneration and promotes neurovascular unit recovery after SCI [ 163 ]. Yuan et al [ 110 ] found that pericyte exocytosis could promote blood flow, improve vascular endothelial function, and protect the BSCB via the PTEN/AKT signalling pathway, which is beneficial for SCI recovery.…”
Section: Mechanisms By Which Exosomes Repair Scimentioning
confidence: 99%
“…Vascularization facilitates nerve regeneration and promotes neurovascular unit recovery after SCI [ 163 ]. Yuan et al [ 110 ] found that pericyte exocytosis could promote blood flow, improve vascular endothelial function, and protect the BSCB via the PTEN/AKT signalling pathway, which is beneficial for SCI recovery.…”
Section: Mechanisms By Which Exosomes Repair Scimentioning
confidence: 99%
“…The organization of the vascular wall is well structured and consists of three different main functional layers: the intima, a single layer of endothelial cells, which provides an interface between blood and smooth muscle and contains vascular stem cells which are CD34 and c-kit-positive; the media, including smooth muscle cells, collagen and elastin; and the adventitia composed of undifferentiated dendritic cells, connective tissue, vasa vasorum and other cells including fibroblasts, pericytes, and cells CD34, Sca-1, c-kit, NG2 and GII1-positive. This well-organized vascular structure can deal with injuries that are often caused by several acute and chronic diseases including hypertension [ 2 ], atherosclerosis [ 3 ], diabetes [ 4 , 5 ], trauma [ 6 ], occlusions [ 7 ], hypoxia [ 8 ], primary cancerous lesions, and metastases [ 9 ] as well as catheter interventions [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The spinal cord microenvironment in the secondary injury phase produces large amounts of reactive oxygen species (ROS) (e.g., H 2 O 2 ). , The ROS cannot be metabolized in a timely manner and form accumulation, leading to local ischemia, hypoxia, and inflammatory cascade response . This further results in axonal degeneration, demyelination, and neuronal apoptosis. , Therefore, inhibiting the hyperaccumulation of ROS and alleviating the hypoxic environment are effective strategies in the treatment of SCI.…”
Section: Introductionmentioning
confidence: 99%
“…11 This further results in axonal degeneration, demyelination, and neuronal apoptosis. 12,13 Therefore, inhibiting the hyperaccumulation of ROS and alleviating the hypoxic environment are effective strategies in the treatment of SCI.…”
Section: Introductionmentioning
confidence: 99%